HRM Unleashed: Modelling Employee Engagement Through the Mediating Lens of Job Satisfaction with SEM - Gouthami, K.; Kumari, S. Srilalitha G; Sheshadri, Thejasvi; Sharma, Neha; Fatin; Karumuri, Venkateswarlu (Indian Journal of Information Sources and Services, 2026)
Examining the dynamic link between employee engagement, job satisfaction, and organizational results using Structural Equation Modelling (SEM) is the subject of this study. This research uses Cronbach’s alpha, composite reliability, and confirmatory factor analysis to assess the validity and reliability of the construct measures. The respondents come from a wide range of backgrounds. The findings demonstrate a high degree of validity and internal consistency at the dimension level. Organizational outcome, employee engagement, and work satisfaction are all significantly correlated, according to SEM results. By acting as a mediator between engagement and results, work satisfaction plays a pivotal role in the creation of organizational performance, according to the mediation study. The amount of explained variance (R-squared) and effect sizes provide evidence of good model fit, especially when it comes to the prediction of productivity and organizational citizenship behavior. The model also has an out-of-sample predictive power in PLS Predict analysis. In sum, the study gives us a strategic idea of the need to generate participatory and satisfaction levels as a means of ensuring excellence in terms of organizational results and offers programs that HR managers and policy-behaviorists can use in order to enhance the effectiveness of the workforce and their retention.